CHARACTERISTICS AND MANAGEMENT OF PEDIATRIC CATARACT AT UNIVERSITAS TANJUNGPURA HOSPITAL 2019-2021: Oral Presentation - Observational Study - Ophthalmologist - MUHAMMAD ASRORUDDIN; WIWIK WINDARTI; YESSLYN YULIANTO (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : One of the causes of blindness in children that can be treated is cataracts. The prevalence of childhood cataracts in Asia is the highest in the world at 7.43 per 10,000 children. There were 4,270 children in Indonesia who experienced blindness due to cataracts in 2017. Data on childhood cataracts in West Kalimantan is still limited. However, the prevalence of blindness in West Kalimantan is the highest in Indonesia at 1.6%. Characteristics of pediatric cataract patients need to be known to assist in diagnosis and treatment so that the risk of blindness in children can be prevented. This study is to describe cataracts in children at Universitas Tanjungpura Hospital in 2019-2021. Methods : This study used a cross-sectional descriptive design. Data collection was obtained from the medical records of pediatric cataract patients at the Universitas Tanjungpura Hospital during 2019-2021. Results : The total number of pediatric cataract patients obtained from medical records during 2019-2021 was 27 patients, consisting of 8 girls and 19 boys. Congenital cataracts were the most common cataracts (59%) and the most diagnosed age was in the 0-1 year group. Bilateral cataracts (48%) were almost as numerous as unilateral cataracts (52%). The most common visual acuity before and after surgery was fixating and following object (60%). Conclusion : Cataracts in children at Universitas Tanjungpura Hospital in 2019-2021 were dominated by congenital cataracts, diagnosis age was at 0-1 years, bilateral and unilateral, male gender, and visual acuity before and after surgery was fixating and following object.